Uma metodologia de atenuacão de ruído transmitido por lajes utilizando absorvedores dinâmicos de vibração - Holanda, Ricardo Victória de (2012)
In the construction industry there is a tendency to lightweight and slender buildings, and occurs as a consequence of the worsening in acoustic comfort, due to use of materials with higher transmissibility of vibration. Preliminary studies indicate that the noise impact caused by the slabs is the main source of nuisance in apartments, noise is transmitted through the structure due to the vibratory processes, so one possible solution is to reduce the slab vibration. This paper proposes the use of dynamic vibration absorbers (ADV), secondary device that is added to the primary structural system (slab), whose vibration or noise want to attenuate. The method of operational modal analysis (AMO) with transient excitation in conjunction with the techniques in the time domain, with Least Squares Complex Exponential (LSCE) and the Stochastic Subspace Identification (SSI) carried out the modal characterization of the slab, then modeled in finite elements. The ADV s are calculated by the slab modal parameters, using the technique developed by Espíndola and Silva (1992), who introduced the concept of equivalent parameters for generalized viscoelastic absorbers. The tuning frequency and the ADV s positions are defined by the optimization algorithm. The proposal validation was performed by a finite elements model of the room, considering fluid-structure interaction (FSI), with and without the ADV\'s. It was obtained 16 dB attenuation of noise (linear weighting integration impact).